Sex Determination from Clavicle Bone for Punjab Zone (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Determination of sex from the skeleton is possible only when all the bones were available. The clavicle has been described as a useful bone for the metric determination of sex in Punjab zone. In the present study 100 clavicles (78males and 22 females) were taken from Department of Anatomy, Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar. The param eters like Maximum length, Weight and circumference at midshaft circumference of the clavicle were taken and demarking points were evolved for identification of sex for the various measure ments of the clavicles of the Punjab zone.
Keywords: Clavicle; Circumference; Midshaft; Demarking points